Affiliate performance feedback and technology innovation: The mediating effect of the parent’s response - Zheng, Li; Sun, Binbin (Frontiers in Psychology, 2023)
The relationship between firm performance feedback and technology innovation has been studied extensively, but limited attention has been paid to factors that mediate this relationship. We examine how a parent firm addresses an affiliate’s performance level and its influence on the affiliate’s technology innovation. Integrating the behavioral theory of the firm and the concept of parent functions, we argue that the parent firm addresses the affiliate’s performance level in two ways: hierarchy management and resource allocation. Specifically, unlike the case of outperforming affiliates, the parent firm facilitates the technology innovation of underperforming affiliates through hierarchy management and resource allocation. Regression analyses of 2010–2020 data of listed affiliates belonging to Chinese business groups provide strong evidence supporting our conjecture. Our study sheds light on the importance of considering the parent’s influence when affiliates adopt technology innovation in light of its performance feedback.